2000
DOI: 10.1046/j.1365-8711.2000.03473.x
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of galaxies around radio quasars at 0.5≤z≤0.8

Abstract: A B S T R A C TWe have observed the galaxy environments around a sample of 21 radio-loud, steepspectrum quasars at 0X5 # z # 0X82Y spanning several orders of magnitude in radio luminosity. The observations also include background control fields used to obtain the excess number of galaxies in each quasar field. The galaxy excess was quantified using the spatial galaxy±quasar correlation amplitude, B gq , and an Abell-type measurement, N 0.5 . A few quasars are found in relatively rich clusters, but on average, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
97
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(109 citation statements)
references
References 97 publications
12
97
0
Order By: Relevance
“…Yee & Green (1987), Ellingson et al (1991), Yee & Ellingson et al (1993) and Wold et al (2000) have shown evidence of the connection between radio emission and galaxy clustering around QSOs. They found differences between the environment of radio-loud and radio-quiet quasars.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Yee & Green (1987), Ellingson et al (1991), Yee & Ellingson et al (1993) and Wold et al (2000) have shown evidence of the connection between radio emission and galaxy clustering around QSOs. They found differences between the environment of radio-loud and radio-quiet quasars.…”
Section: Introductionmentioning
confidence: 98%
“…There is much evidence for a connection between the QSO activity and clustering of galaxies (Stockton 1982;Yee & Green 1984Gehren et al 1984;Hutchings et al 1984;Hintzen 1984;Yee 1987;Ellingson et al 1991;Hintzen et al 1991;Yee & Ellingson 1993;Fisher et al 1996;Yamada et al 1997;Sánchez & González-Serrano 1999;Cimatti et al 2000;Wold et al 2000). It seems that interaction/merging processes amoung cluster galaxies could play a fundamental role in the origin/feeding process of the nuclear activity.…”
Section: Introductionmentioning
confidence: 99%
“…There is also some evidence that HERGs occupied richer environments in earlier epochs (e.g. Harvanek et al 2001;Belsole et al 2007;Ramos Almeida et al 2013), suggesting evolution of the large-scale environment; conversely, Wold et al (2000) and McLure & Dunlop (2001) found no evidence of evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Belsole et al (2007) and Ineson et al (2013) used X-ray luminosity within the virial radius and R500 respectively. The other studies cited above all used optical methods -a variation on the 'nearest neighbours' method (Best 2004); galaxy counts above a specified magnitude within 1 Mpc radius (Gendre et al 2013); and the galaxy-galaxy spatial covariance function Bgg calculated within a variety of radii depending on the image size (Harvanek et al 2001;Hardcastle 2004;Wold et al 2000 Ledlow et al 2003;Ineson et al 2013), but with a large amount of scatter so conversion between the methods is unreliable.…”
Section: Introductionmentioning
confidence: 99%
“…Although some of these EROs were later shown to lie in the foreground of the radio galaxies (Graham & Dey 1996), probing the fields around high-redshift, radio-loud AGNs (active galactic nuclei) has been a promising method of finding high-redshift galaxies. Luminous quasars and radio galaxies are often associated with high-density galaxy environments (Ellingson, Yee, & Green 1991;Hill & Lilly 1991;Wold et al 2000;Best 2000;Venemans et al 2002;Best et al 2003), and the rich environments are often interpreted as clusters or groups of galaxies hosting the AGNs. By combining a targeted search with a color criterion like that of EROs, high-redshift, early-type galaxies can be effectively filtered out from the numerous foreground galaxies.…”
Section: Introductionmentioning
confidence: 99%